Empatia: uma (des) construção teórica e clínica - Pereira, Nathalia Carballeira (2014)
This paper aims to reflect on the importance of empathy in the therapeutic relationship, seeking to verify their facilitative role in establishing the therapeutic relationship and consequent success in the analytic encounter. Text of the complete works of Carl Gustav Jung and articles over the past decade that addressed directly the issue within the field of analytical psychology were used. The discussion was conducted from possible congruencies and contradictions between the definition of empathy described by contemporary philosophy, by C G. Jung and post Jungian authors with a focus on clinical practice. The work has broadened the understanding of empathy as means of opening space for images into consciousness from both the patient and the therapist (when open to) when it comes to a relationship of alterity conducted by Eros